PERENCANAAN PROGRAM KOMUNIKASI PADA PROGRAM MAGANG DALAM MENINGKATKAN SKILL DAN KNOWLEDGE MAHASISWA (STUDI PADA MAHASISWA GUNADARMA DALAM PROGRAM MAGANG DI MEDIA RADIO MEGASWARA BOGOR) - Yeni Nuraeni; Rina Astriani (Asosiasi Dosen Muda Indonesia, 2023)
The purpose of this study was to find out how to plan a communication program through an collaboration educational institutions with conventional media (radio). The theory this study is symbolic interaction, Mead with the communication program planning model, Smith. and the concept of Skill and Knowledge. The methodology is qualitative. Based on the results of research through observation, documentation and interviews, the concluded is the internship program carried out by Gunadarma students was successful in going through several stages, namely the situation analysis stage - target setting - strategy design - tactic selection - action plan - control and monitoring and evaluation. The implementation of skills, knowledge, and attitudes can be identified through the development of skills and knowledge including problem solving that students can do after carrying out an internship program in the radio media production program division